Optimalisasi Manajemen Sumber Daya Manusia dalam Menghadapi Beban Administrasi Dosen: Implikasi terhadap Kualitas Pengajaran di IAIN Curup - Deli Susanti; Idi Warsah; Jumira Warlizasusi (Education Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study explores the impact of administrative workload on lecturers’ teaching quality at IAIN Curup, focusing on optimizing human resource management. The research addresses the empirical gap regarding how administrative duties affect teaching performance in Islamic higher education institutions. A mixed-methods approach was employed, combining in-depth interviews with lecturers and administrators and a survey of 50 lecturers. Findings indicate that excessive administrative tasks disrupt lecturers’ focus, reduce teaching quality, and lower time management efficiency. The study highlights the importance of HRM strategies that include proportional distribution of administrative duties, digitalization, and participatory and collaborative approaches involving lecturers in workload-related decision-making. Implementing these strategies is expected to enhance teaching quality, lecturer well-being, and institutional efficiency.